2017
DOI: 10.1002/srin.201700149
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behavior and Microstructural Evolution of High Nitrogen Martensitic Stainless Steel 30Cr15Mo1N

Abstract: Hot deformation behavior of high nitrogen martensitic stainless steel 30Cr15Mo1N is investigated by isothermal compression tests at the temperature range of 900-1250 8C and the strain rate range of 0.01-10 s À1 . The results indicate that the activation energy of this alloy (503.5 kJ mol À1 ) is higher than that of conventional martensitic stainless steels. The developed Arrhenius-type constitutive equation considering strain compensation can predict flow stress of 30Cr15Mo1N with good consistency. The critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The change in flow stress level with deformation temperature or strain rate was probably due to an increase in the rate of restoration processes and a decrease in the strain hardening rate [12]. The lower strain rate can provide enough time for energy accumulation, and the higher deformation temperature can accelerate the dissolution of precipitates, dislocation movement and grain boundary migration for the formation of DRX nuclei, which in turn lowered the stress level [12,13]. It is worth mentioning that the flow curves exhibited a prominent oscillation at all temperatures for the lowest strain rate of 0.1 s −1 , while the oscillations were much slower with increasing strain rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in flow stress level with deformation temperature or strain rate was probably due to an increase in the rate of restoration processes and a decrease in the strain hardening rate [12]. The lower strain rate can provide enough time for energy accumulation, and the higher deformation temperature can accelerate the dissolution of precipitates, dislocation movement and grain boundary migration for the formation of DRX nuclei, which in turn lowered the stress level [12,13]. It is worth mentioning that the flow curves exhibited a prominent oscillation at all temperatures for the lowest strain rate of 0.1 s −1 , while the oscillations were much slower with increasing strain rate.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that the flow curves exhibited a prominent oscillation at all temperatures for the lowest strain rate of 0.1 s −1 , while the oscillations were much slower with increasing strain rate. The oscillation phenomenon could be mainly attributed to the reduced accuracy and stability of sensors at the lowest strain rate of 0.1 s −1 , as well as the competing effect between various deformation mechanisms [13]. …”
Section: Methodsmentioning
confidence: 99%
“…These carbides are harmful for the fatigue life and corrosion resistance of MSSs [4,5]. The addition of the element of nitrogen into MSSs is an effective way to reduce the number and size of these large eutectic carbides [6], meanwhile, nitrogen can make these carbides distribute more evenly. Furthermore, nitrogen inhibits the austenite grain growth and the formation of δferrite, strengthens MSSs by interstitial solid solution and precipitation of nitrides [7].…”
Section: Introductionmentioning
confidence: 99%
“…During the hot deformation process, the internal microstructure of metals generally evolves extensively and significantly influences the constitutive behavior of materials [13]. Investigations of the hot deformation behaviors for different martensitic steels(30Cr15Mo1N [14], AISI403/ 403Nb [15], high nitrogen martensitic steel [16], etc) have been carried out carefully, and it was found that the dynamic recrystallization(DRX) occur during the hot deformation conditions. However, the constitutive models in the literatures were established on the basis of Arrhenius equation, which were not quite suitable to give a reasonable description on the mechanism of DRX.…”
Section: Introductionmentioning
confidence: 99%